Comparison of vehicular fuel consumption and CO2 emission before and during the COVID-19 pandemic in Kathmandu valley - Paudel, Paranjaya; Sapkota, Sabal; Gyanwali, Khem; Adhikari, Bikash (Journal of Innovations in Engineering Education, 2021)
In the past few decades, the change in emission and fuel consumption pattern of Kathmandu valley (KV) has been increasing rapidly. But due to the COVID-19 pandemic, it was disrupted for a certain time. The main aim of this study is to compare the carbon dioxide (CO2) emission before and during the COVID-19 pandemic for KV based on the motor-spirit (MS) & high-speed-diesel (HSD) fuel consumed by the vehicles. From the fuel sales data provided by Nepal Oil Corporation (NOC), CO2 emission was calculated as per the Tier 1 approach given in the guidelines provided by the Intergovernmental Panel on Climate Change (IPCC). 14.9% of total fuel sales of Nepal was consumed in KV alone by road transport for fiscal year (FY) 2019/20. KV area produced 9,14,352 tonnes of CO2 emissions from the transportation sector in the FY 2019/20 from the corresponding 2,92,260 kiloliters of fuels. CO2 emission had declined by 80.11% after the lockdown was implemented in the valley but later on, till Asar (Mid June – Mid July) it again rose to 65%.